1972
DOI: 10.1159/000230613
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Analyses of Birch Pollen Antigens, with Special Reference to the Allergenic Components

Abstract: Birch pollen contains some ten antigenic components, demonstrable with immunodiffusion methods. One or two of these antigens differ from the others by a remarkable resistance to heat and extreme pH. In addition, these thermostable antigens are responsible for the major allergenic activity of birch pollen extracts and are more readily extracted from birch pollen than the other antigens. The allergenic thermostable antigens of birch pollen have counterparts, particularly in the pollen of alder, but also to some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
43
0

Year Published

1976
1976
1995
1995

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 8 publications
7
43
0
Order By: Relevance
“…Only one or two of these are allergcnically active [2]. These antigens have been found to occur as separate precipitinogens after heat treatment of a birch-pollen extract and in the allergen-active fractions obtained after gel filtration of the extracts [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one or two of these are allergcnically active [2]. These antigens have been found to occur as separate precipitinogens after heat treatment of a birch-pollen extract and in the allergen-active fractions obtained after gel filtration of the extracts [3].…”
Section: Discussionmentioning
confidence: 99%
“…Bei.in [2] has shown that birch pollen contains some 10-15 1 Presented in part at the 7th F.uropean Congress of Allergology, W. Berlin, September 1968.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An aqueous extract of birch pollen contains six allergens (by CRIE, crossed radioimmunoelectrophoresis), but only one fulfills the conditions of a major allergen; Bet Y I (antigen 23) (Belin 1972a, 19726, Viander et al 1979, Apold et al 1981, Vik et al 1982, Ipsen & Lowenstein 1983, Marsh et al 1986) is of 17 kD (PI 5.25, 5.5, 5.0), a thermostable, cytosolic protein consisting of 159 amino acids. Bet Y I has at least three isoforms, which probably constitute more than 90-95% of the total allergen content (Vik et al 1983, Vik & Elsayed 1986, Valenta et al 1991a, Jilek et al 1993.…”
Section: (Maizuscrandt Accepted 5 Sepienzber 1995)mentioning
confidence: 99%
“…Although birch pollen contains at least 10-15 distinct antigens [2] only 1 or 2 of these are associated with the major allergenic activity. The question then arises whether the allergenic components are allergenic be cause they have certain characteristics which enable them to reach reaginproducing cells or because they have a special ability to stimulate poten tially reagin-producing cells to antibody formation.…”
mentioning
confidence: 99%